E-010 Features of dissections on high resolution MRI. (12th July 2011) - Hui, F; Mahmoud, S; Toth, G; Ken, U; Hajj-Ali, R; Jones, S
Abstract : Introduction: High resolution MR imaging has been used to evaluate vessel walls in atherosclerotic disease as well as vasculitides in order to characterize wall thickness and enhancement. High resolution MRI may also be useful in characterizing dissections and may offer additional information not available from catheter angiography. Methods: This is a retrospective review of 75 patients who underwent high resolution contrast enhanced imaging of the neurovasculature. Four patients with a history of dissection were included in this retrospective review. Re analysis of the exams was performed by two attending neuroradiologists with comparison to other relevant imaging modalities including cerebral angiography, conventional magnetic resonance and CT. Results: Images from the high resolution magnetic resonance examinations demonstrate wall enhancement in dissected vessels as well as the dissection flap. The dissected vessel walls demonstrate robust enhancement even in the early phases. Static or slow flowing blood may interfere with the nulling effect of the saturation pulse, so high signal of intravascular components should be interpreted with care. Intravascular thrombus was identifiable in one case that was not detectable on cerebral angiogram. Wall thickness and outer diameter can be assessed on HRMR. Conclusion: High Resolution MRI of intracranial dissections may yield information about angioarchitecture not discernible by conventional imaging. Further investigation is warranted.